2010
DOI: 10.1158/0008-5472.can-10-1671
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ALK, PI3K/MEK, and HSP90 in Murine Lung Adenocarcinoma Induced by EML4-ALK Fusion Oncogene

Abstract: Genetic rearrangements of the anaplastic lymphoma kinase (ALK) kinase occur in 3% to 13% of non-small cell lung cancer patients and rarely coexist with KRAS or EGFR mutations. To evaluate potential treatment strategies for lung cancers driven by an activated EML4-ALK chimeric oncogene, we generated a genetically engineered mouse model that phenocopies the human disease where this rearranged gene arises. In this model, the ALK kinase inhibitor TAE684 produced greater tumor regression and improved overall surviv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
147
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(158 citation statements)
references
References 51 publications
9
147
1
1
Order By: Relevance
“…This makes them dependent on molecular chaperones to remain stable. Indeed, EML4-ALK variant 1 has been shown to be highly unstable, and it may be more sensitive to Hsp90 inhibition than any other client protein yet observed (8,9,25). The sensitivity of variants 1 and 2 are due to protein mis-folding resulting in exposure of hydrophobic residues that recruit Hsp90, which is supported by the observation that this sensitivity is not found in variants 3 and 5 (12).…”
Section: Discussionmentioning
confidence: 95%
“…This makes them dependent on molecular chaperones to remain stable. Indeed, EML4-ALK variant 1 has been shown to be highly unstable, and it may be more sensitive to Hsp90 inhibition than any other client protein yet observed (8,9,25). The sensitivity of variants 1 and 2 are due to protein mis-folding resulting in exposure of hydrophobic residues that recruit Hsp90, which is supported by the observation that this sensitivity is not found in variants 3 and 5 (12).…”
Section: Discussionmentioning
confidence: 95%
“…However, a recurring theme in the clinical experience with many targeted kinase inhibitor drugs, including imatinib and crizotinib, is that their long-term efficacy is often hampered by the invariable development of acquired resistance, commonly arising due to the acquisition of secondary mutations in their respective kinase targets (34,35). We and others have previously shown that HSP90 inhibition is an effective approach for overcoming oncogenic EML4-ALK activity in non-small cell lung cancer (18,36,37). Significantly, ganetespib also displayed potent activity against a variety of acquired ALK mutations that confer crizotinib resistance in multiple experimental models and in the clinical setting (18).…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, the fusion partner (e.g., EML4) is believed to mediate ligand-independent oligomerization of ALK, resulting in constitutive ALK kinase activation (2)(3)(4). In cell line and genetically engineered mouse models, EML4-ALK serves as a potent oncogenic "driver," and cancers with this translocation are highly sensitive to ALK kinase inhibition (5,6). Recently, a tyrosine kinase inhibitor (TKI) targeting ALK, crizotinib (PF-02341066), was examined in a phase 1 trial (7).…”
mentioning
confidence: 99%